EFEKTIVITAS PROGRAM SLRT MELALUI PELAYANAN MOBIL KELILING OLEH DINAS SOSIAL KABUPATEN PASAMAN - Sri Yuni Hartika; Jumiati Jumiati (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This study aims to determine the effectiveness of the integrated Referral Service System (SLRT) program through Mobile Car Service by the Pasaman District Social Service and describe the constraint that affect the effectivenessof the SLRT program through Mobile Car Service. This research is motivated by the existence of service innovations carried out by the Pasaman District Sosial Service which provides mobile service for people who want to make complaints or complaints about poverty alleviation programs. This research is based on aqualitative method with a descriptive approach. The data collection instruments were trought interviews, observation and documentation. The result of this research is that the effectiveness of the integrated referral service system (SLRT) program through mobile car serviceby the Pasaman District Social Office is less effective. This is evidenced by the study of the effectiveness of the SLRT program through Mobile Car Service by the Pasaman District Social Service which has not been well socialized to the community, the availability of facilities and infrastructure is not sufficient and also program supervision is not optimal. Furthermore, there are also obstacles in making the Mobile SLRT Program effective, namely internal constraints in the form of limited facilities and infrastucture as well as budget resources and external constraints in the form of communication and target groups.